Advancements in MAPK signaling pathways and MAPK‐targeted therapies for ameloblastoma: A review. (3rd February 2019) - You, Zhu; Liu, Shao‐Peng; Du, Jing; Wu, Yi‐Hua; Zhang, Shi‐Zhou
Abstract : Numerous signal transduction pathways are closely associated with the occurrence, development, and prognosis of ameloblastoma (AM). Mitogen‐activated protein kinase (MAPK) is a serine/threonine‐specific protein kinase that transduces intracellular signals in critical cellular phenomena. A number of recent analyses have reported that the MAPK signaling pathway contributes significantly to AM. High‐throughput DNA sequencing methods, such as next‐generation sequencing using Illumina have yielded advancements in studies on MAPK signaling pathways and their association with AM; in particular, BRAF V600E is mediated by the activation of the Ras/Raf/MAPK pathway. This review discusses advancements in studies on MAPK signaling pathways and MAPK‐targeted inhibitors or antibodies, along with the merits and demerits of MAPK‐targeted therapies, finally followed by a discussion regarding more efficient potential MAPK‐targeted therapies to treat AM with few side effects, thereby providing novel insights into targeted therapy for AM.